Differential effects of obesity on eosinophilic vs. non-eosinophilic asthma subtypes. (3rd July 2018) - Mukadam, Seema; Zacharias, Jamie; Henao, Maria Paula; Kraschnewski, Jennifer; Ishmael, Faoud
ABSTRACT: Objective : Asthma is a heterogeneous disease composed of multiple disease subtypes. Obesity may worsen asthma, although the mechanism is poorly understood and its effects on different subtypes are not well characterized. We sought to determine whether obesity affects eosinophilic asthma differently from non-eosinophilic asthma. Methods : Charts of 196 persistent asthmatics were reviewed. Subjects were categorized according to BMI (obese ≥ 30 kg/m 2 ) and blood eosinophilia based on two different cutoffs (≥200 or ≥400 cells/µl): eosinophilic, non-obese (E-NO), eosinophilic, obese (E-O), non-eosinophilic, non-obese (NE-NO), and non-eosinophilic, obese (NE-O). We analyzed clinical parameters across these groups to determine associations with obesity and/or eosinophilia. Results : Obesity was highly prevalent in our population (50.5%, 99/196). The majority of asthmatics were female (75.5%), though the ratio was lower in the E-NO group (56%). The NE-NO group was associated with lowest asthma severity, lower atopy, and less medication use. Regardless of eosinophilia, obesity was associated with higher inhaled corticosteroid doses and lower FVC% predicted than their non-obese counterparts. Obesity was associated with reduced FEV1% only in the non-eosinophilic group. Eosinophilia was also associated with reduced FEV1% in the non-obese subjects, but FEV1% was not further reduced in the E-O group compared to the E-NO and NE-O groups. Similar findings were observed regardless of whether the blood eosinophil cutoff was 200 or 400 cells/ µl. Conclusion : Multiple clinical features of asthma are adversely affected by obesity, which may affect eosinophilic and non-eosinophilic subtypes differently.